Civic Education Learning Based on Law-Related Education in The Development of Student Legal Attitude - Baeihaqi Baeihaqi; Kokom Komalasari (Jurnal Civicus, 2020)
This study aims to describe the implementation of Pancasila and Civic Education learning by using the Law-Related Education (LRE) approach in the learning process of teaching and learning activities. This study uses a quantitative approach with a quasi-experimental method covering two research samples and giving different treatments. The control class uses conventional learning, the experimental class uses the Law-Related Education approach. This research is located at SMA Laboratorium Percontohan UPI. The results of the study indicate that the LRE approach in Civics learning is relevant to be used in the teaching and learning process in the context of legal material in Civics. Through the integration of LRE, which increases the knowledge, skills, and values needed by students to work effectively in a pluralistic and democratic society, the rule of law, so the integration of Civics and LRE is a significant solution effort to develop students' legal attitudes. Therefore, the implementation of legal learning in Civics must be carried out in an integrative, interactive, and collaborative manner. This has implications for the development of legal awareness for students to find social problems, especially those related to law in the community.